Relationship between knowledge-based risk and risk identification - Amine Nehari Talet; Louay Karadsheh; Samer Alhawari; Hana Hunaiti (South African Journal of Business Management, 2018)
Background: Knowledge-based risk processes are turning into a major aspect inside establishments because they can limit the likelihood and effect of information technology (IT) project threats and catch opportunities amid the life cycle of an IT project.Objectives: The objective of the article is to propose a model that describes the amalgamation of knowledge-based risk processes (knowledge-based risk capture and knowledge-based risk discovery) and knowledge-based risk repositories to support risk identification.Method: This article adopts a quantitative research approach using surveys, with questionnaires composed from 135 employees in 10 IT companies in Jordan. The researchers employed smart partial least squares analysis to examine all of the hypotheses.Results: The results propose that the adoption of knowledge-based risk capture and knowledge-based risk discovery has a positive impact on risk identification, which is mediated by knowledge-based risk repositories.Conclusion: Knowledge-based risk processes and knowledge-based risk repositories are generally utilised as a part of IT projects to effectively and successfully support risk identification.
Keywords: 650